STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS VA PADA MATA PELAJARAN MATEMATIKA DI SDN 01 MENTAWA DESA TANJUNG MEKAR KABUPATEN SAMBASTAHUN PELAJARAN 2023-2024 - Tara Nopika Apriani; Hifza; Mutazam (CV. ADIBA AISHA AMIRA, 2026)
This thesis discusses Teachers' Strategies in Improving the Numeracy Ability of Class VA Students in Mathematics Subjects at SDN 01 Mentawa, Tanjung Mekar Village, Sambas Regency, Academic Year 2023-2024. This research has three objectives, namely: 1) Preparation of teachers' strategies in improving students' numeracy skills. 2) Teachers' strategic steps in improving students' numeracy skills. 3) Teacher evaluation in improving students' numeracy skills. This research uses a qualitative approach and a type of phenomenological research. Data collection techniques use interviews, observations, and documentation. Data analysis techniques use data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that: 1. The preparation of teachers' strategies in improving students' numeracy skills in the VA class of SDN 01 Mentawa Tanjung Mekar Village, Sambas Regency for the 2023-2024 school year is to prepare a learning plan before teaching because it is a reference for the learning process, setting learning goals, and preparing the time needed for each learning to be optimal. 2. Teachers' strategy steps in improving students' numeracy skills in the VA class of SDN 01 Mentawa, Tanjung Mekar Village, Sambas Regency, for the 2023-2024 school year, are teachers' strategies in improving students' or students' numeracy skills in the context of education, strategy refers to methods or techniques used by educators to facilitate learning and achieve desired results. 3. Teacher evaluation in improving students' numeracy skills in the VA class of SDN 01 Mentawa Tanjung Mekar Village, Sambas Regency for the 2023-2024 school year is as a teacher conducting an assessment to measure the development of students' numeracy skills and teachers provide tests in the form of multiple-choice questions, essays and so on.